Notes from the Millennium Villages Project - Bonds, Matt; Fraden, Max (Consilience, 2008)
Matt Bonds and Max Fraden document their experience unrolling a health insurance subsidization scheme in the Millennium Village in Mayenge, Rwanda. The Millennium Villages Project aims to achieve the eight Millennium Development Goals. These goals outline a global partnership to reduce extreme poverty with specific focuses on hunger, education, gender equality, health, and environmental sustainability. Matt and Max comment on critical lessons learned and observations on the field of sustainable development from their work in Rwanda.